A dose-ranging, parallel group, split-face, single-blind phase II study of light emitting diode-red light (LED-RL) for skin scarring prevention: study protocol for a randomized controlled trial - Nguyen, Julie K.; Weedon, Jeremy; Jakus, Jeannette; Heilman, Edward; Isseroff, R. Rivkah; Siegel, Daniel M.; Jagdeo, Jared R. (Current controlled trials in cardiovascular medicine, 2019)
Background Skin fibrosis is a significant global health problem that affects over 100 million people annually and has a profoundly negative impact on quality of life. Characterized by excessive fibroblast proliferation and collagen deposition, skin fibrosis underlies a wide spectrum of dermatologic conditions ranging from pathologic scars secondary to injury (e.g., burns, surgery, trauma) to immune-mediated diseases. Effective anti-scarring therapeutics remain an unmet need, underscoring the importance of developing novel approaches to treat and prevent skin fibrosis. Our in vitro data show that light emitting diode-red light (LED-RL) can modulate key cellular and molecular processes involved in skin fibrosis. In two phase I clinical trials (STARS 1 and STARS 2), we demonstrated the safety and tolerability of LED-RL at fluences of 160 J/cm 2 up to 480 J/cm 2 on normal human skin. Methods/design CURES (Cutaneous Understanding of Red-light Efficacy on Scarring) is a dose-ranging, randomized, parallel group, split-face, single-blind, mock-controlled phase II study to evaluate the efficacy of LED-RL to limit post-surgical skin fibrosis in subjects undergoing elective mini-facelift surgery. Thirty subjects will be randomly allocated to three treatment groups to receive LED-RL phototherapy or temperature-matched mock irradiation (control) to either periauricular incision site at fluences of 160 J/cm 2 , 320 J/cm 2 , or 480 J/cm 2 . Starting one week post-surgery (postoperative days 4–8), treatments will be administered three times weekly for three consecutive weeks, followed by efficacy assessments at 30 days, 3 months, and 6 months. The primary endpoint is the difference in scar pliability between LED-RL-treated and control sites as determined by skin elasticity and induration measurements. Secondary outcomes include clinical and photographic evaluations of scars, 3D skin imaging analysis, histological and molecular analyses, and adverse events. Discussion LED-RL is a therapeutic modality of increasing importance in dermatology, and has the potential to limit skin fibrosis clinically by decreasing dermal fibroblast activity and collagen production. The administration of LED-RL phototherapy in the early postoperative period may optimize wound healing and prevent excessive scarring. The results from this study may change the current treatment paradigm for fibrotic skin diseases and help to pioneer LED-RL as a safe, non-invasive, cost-effective, portable, at-home therapy for scars. Trial registration ClinicalTrials.gov, NCT03795116 . Registered on 20 December 2018.